SharePoint 2007 Development Recipes : A Problem-Solution Approach - Gerow, by Mark E. (Apress, 2013)
Like a cookbook, SharePoint 2007 Development Recipes assumes a certain level of proficiency on the part of the reader. I’ll assume you know how to create the basic .NET project types: console, ASP.NET, and ASP.NET web service. That being the case, I won’t do a lot of setup for the recipes, just launch in to where the coding begins.